2017
DOI: 10.1089/hum.2017.187
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal Adeno-Associated Virus Mediated Gene Delivery and Expression of Human Iduronidase in the Central Nervous System: A Noninvasive and Effective Approach for Prevention of Neurologic Disease in Mucopolysaccharidosis Type I

Abstract: Mucopolysaccharidosis type I (MPS I) is a progressive, multi-systemic, inherited metabolic disease caused by deficiency of α-L-iduronidase (IDUA). Current treatments for this disease are ineffective in treating central nervous system (CNS) disease due to the inability of lysosomal enzymes to traverse the blood-brain barrier. A noninvasive and effective approach was taken in the treatment of CNS disease by intranasal administration of an IDUA-encoding adeno-associated virus serotype 9 (AAV9) vector. Adult IDUA-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 59 publications
3
45
0
Order By: Relevance
“…Whether or not placing the subject in the Trendelenburg position right after infusion can potentiate the efficacy of brain transduction by this procedure remains debated (Meyer et al, 2015). Intranasal Delivery for Brain Transduction While the primary indication for intranasal AAV delivery has been to target the respiratory tract, this non-invasive gene transfer strategy has also been recently applied for the treatment of MPS I (Belur et al, 2017) (Figure 2). Adult IDUA-deficient mice were instilled intranasally with an AAV9.IDUA, and a complete restoration of enzyme activity to normal levels was noticed 5 months post treatment in all parts of the brain, even though the area of AAV transduction remained localized to the olfactory bulb.…”
Section: The Route Of Administration: a Major Variablementioning
confidence: 99%
“…Whether or not placing the subject in the Trendelenburg position right after infusion can potentiate the efficacy of brain transduction by this procedure remains debated (Meyer et al, 2015). Intranasal Delivery for Brain Transduction While the primary indication for intranasal AAV delivery has been to target the respiratory tract, this non-invasive gene transfer strategy has also been recently applied for the treatment of MPS I (Belur et al, 2017) (Figure 2). Adult IDUA-deficient mice were instilled intranasally with an AAV9.IDUA, and a complete restoration of enzyme activity to normal levels was noticed 5 months post treatment in all parts of the brain, even though the area of AAV transduction remained localized to the olfactory bulb.…”
Section: The Route Of Administration: a Major Variablementioning
confidence: 99%
“…Lipid-based NPs have been studied for intranasal drug delivery and this non-invasive strategy approach has been used to assess the efficacy of treatment of neurological manifestation in MPS I disease. Laboratory experiments in mice showed that intranasal administration of an α- l -iduronidase (IDUA) encoding adeno-associated virus serotype 9 (AAV9) vector results in enzyme diffusion into deeper areas of the brain and related reduction of tissue GAG storage materials in the brain [ 39 ]. Intranasal delivery could then potentially be used to treat CNS manifestations of MPS I.…”
Section: Transport At the Bbbmentioning
confidence: 99%
“…However, because the objects used in this test had a very different shape, the latter will be considered as the primary distinctive factor in this report. The delayed non-match to position (DNMP) task evaluates working-and visuospatial memory and has been previously described in the literature [28,29,57]. One trial consists of a sample phase, a progressive time delay interval (20-, 30-, 40-, 50-, or 60-s), followed by a non-match phase ( Figure 2).…”
Section: Methodsmentioning
confidence: 99%
“…Cognition tests of human MPS I patients reflect impaired working memory [26] which may be due to smaller hippocampal volumes [27]. Furthermore, MPS I affected mice show deficits in learning and navigation [28,29], impaired long-term memory and reduced rearing behavior [30]. Despite reports of behavioral and cognitive differences in MPS I affected mice [31] and humans [26], very little has been described in dogs.…”
Section: Introductionmentioning
confidence: 99%